Muamalah Fiqh Analysis of Murabahah - Mohammad Ghozali; Akhmad Novandi Nurtajuddin; Akmal Hibatullah Ramadhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Murabahah as buying and selling where the owner of the goods mentions the purchase price of the goods, then takes advantage of the buyer by saying